(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article phenomenon of semantic transformation of lexeme «grave» is considered in her vividly-conceptual use, co-operation of concepts KHATA / MOHYLA is interpreted as to the opposition binomial.